PANTANG LARANG SEBAGAI BENTUK BUDAYA TABU MASYARAKAT MELAYU SAMBAS DI KECAMATAN SELAKAU - Desinta Zahra Setiani; Widyastuti, Chattri Sigit (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
Pantang larang is part of the taboo culture to do, which if violated will bring bad things. This research aims to find out the form of pantang larang that becomes a cultural taboo to do in the community, as well as the causes obtained when violating it. The method used in this research is the descriptive qualitative method. The data in this study are sentences that contain pantang larang which becomes a cultural taboo to be done by the Sambas Malay community in Selakau District. Meanwhile, the data comes from three informants who are native Sambas Malay in Selakau District. The data was obtained by using the interview method to three informants from Selakau District. Furthermore, the data were analyzed using the commensurate method through comparative historical linguistic studies focusing on taboo theory. This research produces findings in the form of five forms of pantang larang that become taboo culture, namely pantang larang prohibitions related to safety, fear of supernatural beings, activities or activities, gender, and pantang larang related to time. In this case, pantang larang is used as advice that provides moral teaching about life norms and is believed by the Sambas Malay community in Selakau District if violated will have bad consequences in everyday life.